Dual-network antibacterial bone repair material as well as preparation method and application thereof

By depositing mineralized hydroxyapatite on the collagen layer and crosslinking it with antibacterial materials, the dual-network antibacterial bone repair material is solved, and the problem that existing bone repair materials are difficult to have both antibacterial, bone repair and mechanical properties is achieved, and the versatility and efficient performance of the material are achieved.

CN119701090APending Publication Date: 2025-03-28BEIJING BONSCI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411855952.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Existing bone repair materials are difficult to have both antibacterial, bone repair and good initial mechanical properties.

Method used

Dual network antibacterial bone repair material is used to deposit mineralized hydroxyapatite on the collagen layer and cross-link it with the antibacterial material to form a dual network interpenetrating structure to enhance the antibacterial function and mechanical properties of the material.

Benefits of technology

The osteogenesis induction, antibacterial and early good mechanical properties of the material are achieved, and these functions can be taken into account at the same time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119701090A_ABST
    Figure CN119701090A_ABST
Patent Text Reader

Abstract

The invention provides a dual-network antibacterial bone repair material and a preparation method and application thereof, and relates to the technical field of biological materials, the dual-network antibacterial bone repair material comprises mineralized collagen and an antibacterial material; the mineralized collagen comprises a collagen layer and hydroxyapatite deposited and mineralized on the collagen layer; the antibacterial material and the collagen layer are mutually crosslinked. The material simulates a bone material of a minimum structural unit of a natural bone, can achieve a better osteogenic induction effect, and has better mechanical properties by taking collagen macromolecules as a scaffold; the mineralized collagen and the antibacterial material are cross-linked to form a double-network interpenetrating structure, the antibacterial material is connected with collagen macromolecules, the antibacterial function is achieved, the collagen macromolecules are indirectly connected through cross-linking of the antibacterial material, and the mechanical property of the material is further improved. The dual-network antibacterial bone repair material can simultaneously have osteogenic induction, antibacterial and early-stage good mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of biomaterials, and in particular to a double-network antibacterial bone repair material and a preparation method and application thereof. Background Art

[0002] Clinically, the repair of bone defects is often accompanied by severe bacterial infections. According to data from the World Health Organization, approximately 1.5 million cases worldwide are caused by severe bone infections. Despite advances in preventive measures and aseptic surgical techniques, there is still an infection rate of 1-2%, and a high incidence of recurrent infections. Even more serious is that the overuse of antibiotics has led to increasing bacterial resistance to traditional drugs such as gentamicin and vancomycin, reducing the effectiveness of existing bacterial treatment strategies. Of course, the microenvironment of bone reconstruction must not only fight infection, but also have properties such as anti-inflammatory and the ability to create favorable space for cell infiltration, which is crucial for bone tissue remodeling.

[0003] At present, there is no bone repair material with both antibacterial and osteoinductive functions in China, and existing products cannot meet the requirements. For example, antibacterial bone implant products: antibiotic bone cement, although such products have good antibacterial effects, they do not have the function of bone repair. Or existing bone repair products, such as Johnson & Johnson's Healos, Geistlich's Biooss, Beijing Aojin Medical Co., Ltd.'s Ikegold, and Tianjin Saining Technology Co., Ltd.'s Bone Cube, although such products have good bone repair effects, they do not have antibacterial functions. Existing antibacterial bone repair materials are obtained by combining antibacterial functional materials with bone repair materials by coating, perfusion or compounding. Currently, there are three main ways to combine antibacterial function with bone implants: metal coating-loaded type, antibacterial agent-infused scaffold type and multi-material composite type. Among them, the metal coating-loaded type is selective for antibacterial agents and only contains antibacterial coating on the surface. The inside of the implant is not antibacterial and is suitable for non-degradable bone implants; the antibacterial agent-infused scaffold type has poor bonding strength and poor uniformity, which can easily lead to rapid local release in the early stage; the current technology of multi-material composite type cannot simultaneously have the advantages of antibacterial, bone repair and good initial mechanical properties.

[0004] For example, although the Chinese patent with application number 202210388852.7 has obtained a bone repair material with both antibacterial and bone-inducing functions, the bioactive ceramics and collagen in its preparation process adopt a simple material mixing method, which makes it difficult to ensure their uniformity and firmness; the Chinese patent with application number 201911043801.5 provides a new idea for the uniform combination of hydroxyapatite and chitosan, and the process is simple, which can be used for reference in the preparation of antibacterial collagen-based bone repair materials, but it is also difficult to have both antibacterial, bone repair and good initial mechanical properties.

[0005] In view of this, the present invention is proposed. Summary of the invention

[0006] One of the purposes of the present invention is to provide a double-network antibacterial bone repair material to solve the technical problem that the bone repair materials in the prior art are difficult to have both antibacterial, bone repair and good initial mechanical properties.

[0007] A second object of the present invention is to provide a method for preparing a double-network antibacterial bone repair material.

[0008] The third object of the present invention is to provide the application of the above-mentioned double-network antibacterial bone repair material or the double-network antibacterial bone repair material prepared by the above-mentioned preparation method in bone tissue regeneration or as or in the preparation of bone defect filling and repair materials.

[0009] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0010] In a first aspect, a dual-network antibacterial bone repair material is provided, comprising mineralized collagen and an antibacterial material;

[0011] The mineralized collagen includes a collagen layer and mineralized hydroxyapatite deposited on the collagen layer;

[0012] The antibacterial material and the collagen layer are cross-linked with each other.

[0013] Furthermore, the mass ratio of hydroxyapatite to collagen is 5:5 to 7:3;

[0014] Preferably, the mass ratio of the antibacterial material to the mineralized collagen is 1:9 to 9:1;

[0015] Preferably, the antibacterial material is modified chitosan, sodium alginate, betaine or curcumin;

[0016] Preferably, the modified chitosan comprises at least one of acylated chitosan, carboxylated chitosan, alkylated chitosan or quaternized chitosan;

[0017] Preferably, the collagen is type I collagen.

[0018] In a second aspect, a method for preparing the above-mentioned double network antibacterial bone repair material is provided, comprising the following steps:

[0019] A. Adding calcium source and phosphorus source according to the formula amount into the collagen slurry to obtain mineralized collagen;

[0020] B. Add mineralized collagen according to the formula amount into the antibacterial material solution for cross-linking to obtain a double-network antibacterial bone repair material.

[0021] Furthermore, the concentration of collagen in the collagen slurry is 1 to 10 mg / mL;

[0022] Preferably, the molecular weight of the collagen is 10 to 200 kDa, preferably 120 to 140 kDa;

[0023] Preferably, the adding of the calcium source and the phosphorus source comprises adding the calcium source and the phosphorus source while stirring;

[0024] Preferably, the calcium ion concentration in the calcium source is 0.1 to 1 mol / L, and the phosphate ion concentration in the phosphorus source is 0.1 to 1 mol / L;

[0025] Preferably, the molar ratio of the added calcium ions to phosphate ions is 2 to 4:2, preferably 3:2;

[0026] Preferably, the rate of adding the calcium source and the phosphorus source is 0.01 to 10 g / min; the stirring speed is 50 to 800 rpm / min;

[0027] Preferably, the calcium source includes at least one of calcium chloride, calcium bicarbonate, calcium bisulfate, calcium nitrate, calcium chlorate, calcium hypochlorite, calcium perchlorate, calcium bisulfite, calcium iodide, calcium bromide or calcium permanganate;

[0028] Preferably, the phosphorus source includes at least one of phosphoric acid, sodium dihydrogen phosphate, trisodium phosphate or sodium hydrogen phosphate;

[0029] Preferably, the concentration of the antibacterial material in the antibacterial material solution is 0.5 to 5 mol / L;

[0030] Preferably, the mineralization further comprises freeze drying to obtain powdered mineralized collagen;

[0031] Preferably, the particle size of the powdered mineralized collagen is 0.2-2 mm.

[0032] Furthermore, the mineralization conditions also include adjusting the pH value to 8 to 12, preferably 11.3, with alkali solution;

[0033] Preferably, the hydroxide ion concentration in the alkali solution is 0.5 to 5 mol / L;

[0034] Preferably, the collagen is type I collagen;

[0035] Preferably, the water content of the mineralized collagen is controlled to be 84-94% before freeze-drying.

[0036] Further, the antibacterial material includes at least one of acylated chitosan, carboxylated chitosan, alkylated chitosan or quaternized chitosan;

[0037] Preferably, freeze-drying is further included after cross-linking.

[0038] Further, the cross-linking includes physical cross-linking or chemical cross-linking;

[0039] Preferably, the chemical cross-linking comprises adding 0.1% to 5% of a cross-linking agent, preferably 1%;

[0040] Preferably, the cross-linking agent comprises glutaraldehyde, genipin, vanillin, tannic acid or sodium tripolyphosphate, preferably glutaraldehyde;

[0041] Preferably, the physical crosslinking is temperature crosslinking;

[0042] Preferably, the temperature crosslinking is a dehydrogenation heat treatment;

[0043] Preferably, the water content of the double network bone repair material is controlled to be 75-95% before freeze drying.

[0044] Furthermore, after mineralization and cross-linking, the material is immersed in deionized water or ethanol to remove impurities.

[0045] In a third aspect, provided is the use of the above-mentioned double-network antibacterial bone repair material or the double-network antibacterial bone repair material prepared by the above-mentioned preparation method in bone tissue regeneration or as or in the preparation of bone defect filling and repair material.

[0046] Furthermore, the bone defect is a non-structural bone defect.

[0047] The present invention provides a double network antibacterial bone repair material, wherein mineralized collagen deposits mineralized hydroxyapatite on the collagen layer to simulate the bone material of the smallest structural unit of natural bone, which can play a good osteoinduction effect, and has good mechanical properties with collagen macromolecules as a scaffold; the mineralized collagen is cross-linked with the antibacterial material to form a double network interpenetrating structure, and the antibacterial material is connected to the collagen macromolecule, which not only has antibacterial function, but also has an indirect connection relationship between the collagen macromolecules through the cross-linking of the antibacterial material, further improving the mechanical properties of the material. The double network antibacterial bone repair material can simultaneously have osteoinduction, antibacterial and good initial mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0048] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0049] Figure 1 A schematic diagram of the cross-linking mechanism of a double-network antibacterial bone repair material provided in Example 1 of the present invention;

[0050] Figure 2This is an infrared spectrum of a double network antibacterial bone repair material provided in Example 5 of the present invention;

[0051] Figure 3 An XRD diffraction pattern of a double-network antibacterial bone repair material provided in Example 5 of the present invention;

[0052] Figure 4 SEM images of different bone repair materials provided by the present invention;

[0053] Figure 5 This is a comparison chart of the in vitro antibacterial effects of different bone repair materials provided by the present invention. DETAILED DESCRIPTION

[0054] Unless otherwise defined herein, scientific and technical terms used in conjunction with the present invention shall have the meanings commonly understood by those of ordinary skill in the art. The meaning and scope of the terms should be clear, however, in the case of any potential ambiguity, the definitions provided herein take precedence over any dictionary or external definitions. In this application, unless otherwise stated, the use of "or" means "and / or". In addition, the use of the term "including" and other forms is non-limiting.

[0055] The methods and techniques of the present invention are generally performed according to conventional methods well known in the art and as described in various general and more specific references that are cited and discussed throughout the present specification unless otherwise indicated.

[0056] In one aspect, the present invention provides a double-network antibacterial bone repair material, comprising mineralized collagen and an antibacterial material;

[0057] The mineralized collagen includes a collagen layer and mineralized hydroxyapatite deposited on the collagen layer;

[0058] The antibacterial material and the collagen layer are cross-linked with each other.

[0059] In the double network antibacterial bone repair material, mineralized collagen is deposited on the collagen layer to form mineralized hydroxyapatite, which simulates the bone material of the smallest structural unit of natural bone. It is similar to the composition of autologous bone, with a porosity of >65%, and can play a good osteoinduction effect. It also uses collagen macromolecules as a scaffold to improve the technical problem of poor mechanical properties of existing bone repair materials. The mineralized collagen is cross-linked with the antibacterial material to form a double network interpenetrating structure. The antibacterial material is connected to the collagen macromolecule to maintain the porous nature of the material. It not only has antibacterial function, but also through the cross-linking of the antibacterial material, there is an indirect connection relationship between the collagen macromolecules, which further improves the mechanical properties of the material. The double network antibacterial bone repair material can simultaneously have osteoinduction, antibacterial and good initial mechanical properties.

[0060] Among them, in the process of cross-linking of mineralized collagen and antibacterial materials to form a double network interpenetrating structure, there will also be self-cross-linking of the collagen layer and self-cross-linking of the antibacterial material, which will further improve the mechanical properties of the material to a certain extent.

[0061] In some specific embodiments, the mass ratio of hydroxyapatite to collagen is 5:5 to 7:3. The composition ratio in this range is close to the composition of bones, forming stable mineralized collagen.

[0062] In some specific embodiments, the mass ratio of the antibacterial material to the mineralized collagen is 1:9 to 9:1, which can take into account both the bone repair effect and the antibacterial effect.

[0063] In some specific embodiments, the antibacterial material is modified chitosan sodium alginate, betaine or curcumin. Chitosan is abundant in sources, non-toxic, low in immunogenicity and has good biodegradability; at the same time, it has good film-forming properties. Experiments have shown that the use of modified chitosan can form a stable cross-linked network and form a double network interpenetrating structure with mineralized collagen, which avoids the problem of bacterial resistance to antibiotics in application. In some specific embodiments, the modified chitosan includes at least one of acylated chitosan, carboxylated chitosan, alkylated chitosan or quaternized chitosan;

[0064] In some specific embodiments, the collagen is type I collagen.

[0065] According to another aspect of the present invention, there is also provided a method for preparing the above-mentioned double network antibacterial bone repair material, comprising the following steps:

[0066] A. Adding calcium source and phosphorus source according to the formula amount into the collagen slurry to obtain mineralized collagen;

[0067] B. Add mineralized collagen according to the formula amount into the antibacterial material solution for cross-linking to obtain a double-network antibacterial bone repair material.

[0068] By adding calcium and phosphorus sources to the collagen slurry for in-situ deposition, the hydroxyapatite mineralized layer formed by the deposition simulates the bone material of the smallest structural unit of natural bone; the mineralized collagen and the antibacterial material are cross-linked to form a double network interpenetrating structure, and the prepared double network antibacterial bone repair material has both osteogenic induction, antibacterial and good initial mechanical properties. Among them, collagen, hydroxyapatite and modified chitosan are currently widely used in clinical practice, with low prices, good biocompatibility, participation in autologous bone metabolism, and can be completely degraded and absorbed.

[0069] In some specific embodiments, the concentration of collagen in the collagen slurry is 1-10 mg / mL, which can maintain good fluidity, more uniform mineralization, and a larger specific surface area.

[0070] In some specific embodiments, the molecular weight of the collagen is 10-200 kDa.

[0071] The molecular weight of collagen may be, but is not limited to, 10 kDa, 30 kDa, 50 kDa, 80 kDa, 100 kDa, 130 kDa, 150 kDa, 180 kDa or 200 kDa, and may be any molecular weight between 10 and 200 kDa, preferably 120 to 140 kDa.

[0072] In some specific embodiments, the adding of the calcium source and the phosphorus source includes adding the calcium source and the phosphorus source while stirring, so as to ensure that a uniform hydroxyapatite mineralization layer is formed on the surface of the collagen.

[0073] In order to ensure uniform and thorough in-situ mineralization, in some specific embodiments, the calcium ion concentration in the calcium source is 0.1-1 mol / L, and the phosphate ion concentration in the phosphorus source is 0.1-1 mol / L. In some specific embodiments, the rate of adding the calcium source and the phosphorus source is 0.01-10 g / min; the stirring speed is 50-800 rpm / min.

[0074] The calcium source includes at least one of calcium chloride, calcium bicarbonate, calcium bisulfate, calcium nitrate, calcium chlorate, calcium hypochlorite, calcium perchlorate, calcium bisulfite, calcium iodide, calcium bromide or calcium permanganate. The phosphorus source includes at least one of phosphoric acid, sodium dihydrogen phosphate, trisodium phosphate or sodium hydrogen phosphate.

[0075] In some specific embodiments, the molar ratio of the added calcium ions to phosphate ions is 2 to 4:2, preferably 3:2.

[0076] In some specific embodiments, the concentration of the antibacterial material in the antibacterial material solution is 0.5-5 mol / L.

[0077] In some specific embodiments, the mineralization further includes freeze-drying to obtain powdered mineralized collagen; freeze-drying to obtain mineralized collagen powder with a certain porosity, which is mixed evenly with the antibacterial solution to avoid changes in the mineralized collagen that affect the bone repair effect and the overall antibacterial effect.

[0078] In some specific embodiments, the particle size of the mineralized collagen powder is 0.2 to 2 mm.

[0079] In some specific embodiments, the mineralization conditions further include adjusting the pH value to 8-12, preferably 11.3, with alkaline solution.

[0080] Specifically, in the mineralization process of the present invention, the pH can be adjusted before adding the calcium source and the phosphorus source, or after adding the calcium source and the phosphorus source. After the mineralization is completed, the naked eye can see obvious floccules, which are mixed with water. The electron microscope can observe that the surface of the collagen is no longer smooth and hydroxyapatite is deposited. The phenomenon is similar to the accumulation of inorganic salts in mineralization, so as to judge that the mineralization is completed.

[0081] Wherein, the concentration of hydroxide ions in the alkali solution is 0.5-5 mol / L; the alkali solution is sodium hydroxide solution, ammonia water, or potassium hydroxide solution.

[0082] In some specific embodiments, the collagen is type I collagen.

[0083] In some specific embodiments, the water content of the mineralized collagen solution is controlled to be 84-94% before freeze-drying.

[0084] In some specific embodiments, the antimicrobial material comprises at least one of acylated chitosan, carboxylated chitosan, alkylated chitosan or quaternized chitosan.

[0085] In some specific embodiments, the cross-linking further comprises freeze-drying.

[0086] In some specific embodiments, the cross-linking comprises physical cross-linking or chemical cross-linking.

[0087] In some specific embodiments, the chemical cross-linking comprises adding 0.1% to 5% of a cross-linking agent, preferably 1%.

[0088] Wherein, the cross-linking agent includes glutaraldehyde, genipin, vanillin, tannic acid or sodium tripolyphosphate, preferably glutaraldehyde;

[0089] In some specific embodiments, the physical crosslinking is temperature crosslinking.

[0090] Wherein, the temperature crosslinking is specifically dehydrogenation heat treatment.

[0091] In some specific embodiments, the water content of the double network bone repair material is controlled to be 75-95% before freeze-drying.

[0092] In some specific embodiments, after mineralization and after cross-linking, the mixture is immersed in deionized water or ethanol to remove impurities, so as to remove excess phosphorus and calcium sources that have not been mineralized, or to remove cross-linking agents and antibacterial materials that have not been cross-linked, and to remove salts generated by the reaction, such as sodium chloride generated by sodium hydroxide and chloride ions after adjusting the pH.

[0093] In a third aspect, provided is the use of the above-mentioned double-network antibacterial bone repair material or the double-network antibacterial bone repair material prepared by the above-mentioned preparation method in bone tissue regeneration or as or in the preparation of bone defect filling and repair material.

[0094] In some specific embodiments, said bone defect is a non-structural bone defect.

[0095] Nonstructural bone defects generally refer to bone defects that do not affect the stability of the bone structure and can be repaired by filling with bone repair materials.

[0096] In specific applications, the double network antibacterial repair material provided by the present invention can not only have the functions of antibacterial property, bone repair and initial mechanical properties at the same time, but also has the characteristics of remodeling. For example, the double network bone repair solution can be perfused and molded into a specific shape before freeze drying in step B during the preparation process, and a double network antibacterial repair material with a specific shape can be obtained after freeze drying. Or before use, the double network antibacterial bone repair material obtained after freeze drying is redissolved in a solvent, perfused and molded into a specific shape, and freeze dried again to obtain a double network antibacterial repair material with a specific shape. Its shape can be block, strip, granular, membrane, columnar, tubular, umbrella-shaped, and other shapes that match the specific application.

[0097] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0098] Example 1

[0099] A dual network antibacterial bone repair material, combined with Figure 1 For illustration, a is a collagen layer, b is hydroxyapatite mineralized on the collagen layer, and c is an antibacterial material. It includes mineralized collagen and antibacterial material; the mineralized collagen includes a collagen layer and hydroxyapatite mineralized on the collagen layer; the antibacterial material is quaternized chitosan, and the quaternized chitosan is cross-linked with hydroxyapatite to form a double network antibacterial bone repair material.

[0100] Among them, the mass ratio of hydroxyapatite to collagen is 1:1, the mass ratio of the antibacterial material to hydroxyapatite is 1:5, and the collagen is bovine type I collagen, type I collagen with a molecular weight of 140kDa.

[0101] Example 2

[0102] A double network antibacterial bone repair material comprises mineralized collagen and antibacterial material; the mineralized collagen comprises a collagen layer and mineralized hydroxyapatite deposited on the collagen layer; the antibacterial material is quaternized chitosan, and the quaternized chitosan is cross-linked with the hydroxyapatite to form a double network antibacterial bone repair material.

[0103] Among them, the mass ratio of hydroxyapatite to collagen is 3:2, the mass ratio of the antibacterial material to hydroxyapatite is 1:5, and the collagen is bovine type I collagen with a molecular weight of 130 kDa.

[0104] Example 3

[0105] A double network antibacterial bone repair material comprises mineralized collagen and antibacterial material; the mineralized collagen comprises a collagen layer and mineralized hydroxyapatite deposited on the collagen layer; the antibacterial material is quaternized chitosan, and the quaternized chitosan is cross-linked with the hydroxyapatite to form a double network antibacterial bone repair material.

[0106] Among them, the mass ratio of hydroxyapatite to collagen is 7:3, the mass ratio of antibacterial material to hydroxyapatite is 1:5, and the collagen is bovine type I collagen with a molecular weight of 120kDa.

[0107] Example 4

[0108] The difference from Example 1 is that sodium alginate is used as the antibacterial material.

[0109] Comparative Example 1

[0110] The difference from Example 1 is that an equal amount of hydroxyapatite is used to cross-link the collagen layer instead of depositing mineralized hydroxyapatite on the collagen layer.

[0111] Embodiments 5 to 8

[0112] A method for preparing a double network antibacterial bone repair material is carried out according to the following steps according to the formula of the double network antibacterial bone repair material of Examples 1 to 4:

[0113] 1) Preparation of mineralized collagen powder

[0114] In a type I collagen slurry with a concentration of 5 mg / mL, a calcium source and a phosphorus source are added to the slurry in sequence at a rate of 2 g / min while stirring, so that the molar ratio of calcium ions to phosphate ions is 3:2. A sodium hydroxide solution with a hydroxide ion concentration of 2 mol / L is used to adjust the pH value of the solution to about 11.3 to obtain a dispersion in which hydroxyapatite is deposited on the surface of the collagen, which is a mineralized collagen solution.

[0115] The mineralized collagen solution is soaked in deionized water solvent to remove impurities, and the moisture content is controlled to 90% for freeze drying and crushing to obtain bone powder, that is, mineralized collagen powder with a particle size of 0.3 mm as raw material A.

[0116] The calcium source is calcium chloride with a calcium ion concentration of 0.5 mol / L, the phosphorus source is sodium phosphate with a phosphate ion concentration of 0.5 mol / L, and the stirring speed is 500 rpm / min.

[0117] 2) Dual network cross-linking

[0118] The antibacterial material is dissolved to obtain an antibacterial solution B, and raw material A is added to the antibacterial solution B according to the formula amount. After the mixture is evenly mixed, the cross-linking agent C glutaraldehyde is added to make the mass concentration of glutaraldehyde 1%, and after cross-linking, the solution is immersed in a deionized water solvent or an ethanol solvent to remove impurities to obtain a double-network bone repair solution; the water content before freeze-drying is controlled to 85%, and after perfusion molding, the solution is freeze-dried to obtain a double-network bone repair material.

[0119] The freeze-drying conditions in this example were -20°C for 48 h.

[0120] Example 9

[0121] A method for preparing a double network antibacterial bone repair material, comprising the following steps according to the formula of the double network antibacterial bone repair material of Example 1:

[0122] 1) Preparation of mineralized collagen powder

[0123] In a type I collagen slurry with a concentration of 5 mg / mL, a calcium source and a phosphorus source are added to the slurry at a rate of 10 g / min while stirring, so that the molar ratio of calcium ions to phosphate ions is 1:1, and a sodium hydroxide solution with a hydroxide ion concentration of 2 mol / L is used to adjust the solution pH to about 11.3 to obtain a dispersion in which hydroxyapatite is deposited on the collagen surface, which is a mineralized collagen solution.

[0124] The mineralized collagen solution is soaked in deionized water solvent to remove impurities, and the moisture content is controlled to 85% for freeze drying and crushing to obtain bone powder, that is, mineralized collagen powder with a particle size of 0.3 mm as raw material A.

[0125] The calcium source is calcium chloride with a calcium ion concentration of 0.1 mol / L, the phosphorus source is trisodium phosphate with a phosphate concentration of 0.1 mol / L, and the stirring speed is 500 rpm / min.

[0126] 2) Dual network cross-linking

[0127] The antibacterial material is dissolved to obtain an antibacterial solution B, and raw material A is added to the antibacterial solution B according to the formula amount. After the mixture is evenly mixed, glutaraldehyde is added to make the mass concentration of glutaraldehyde 1%. After cross-linking, the solution is immersed in a deionized water solvent or an ethanol solvent to remove impurities to obtain a double-network bone repair solution; the water content before freeze-drying is controlled to 85%, and the double-network bone repair material is obtained by freeze-drying after perfusion molding.

[0128] The freeze-drying conditions in this example were -20°C for 48 h.

[0129] Example 10

[0130] A method for preparing a double network antibacterial bone repair material, comprising the following steps according to the formula of the double network antibacterial bone repair material of Example 1:

[0131] 1) Preparation of mineralized collagen powder

[0132] In a type I collagen slurry with a concentration of 10 mg / mL, a calcium source and a phosphorus source are added to the slurry at a rate of 50 g / min while stirring, so that the molar ratio of calcium ions to phosphate ions is 2:1, and a sodium hydroxide solution with a hydroxide ion concentration of 5 mol / L is used to adjust the solution pH to about 11.3 to obtain a dispersion in which hydroxyapatite is deposited on the collagen surface, which is a mineralized collagen solution.

[0133] The mineralized collagen solution is soaked in deionized water solvent to remove impurities, and the moisture content is controlled to 90% for freeze drying and crushing to obtain bone powder, that is, mineralized collagen powder with a particle size of 0.5 mm as raw material A.

[0134] The calcium source is calcium chloride with a calcium ion concentration of 1 mol / L, the phosphorus sources are phosphoric acid and calcium hydroxide with a phosphate ion concentration of 1 mol / L, and the stirring speed is 500 rpm / min.

[0135] 2) Dual network cross-linking

[0136] The antibacterial material is dissolved to obtain an antibacterial solution B, and raw material A is added to the antibacterial solution B according to the formula amount. After the mixture is evenly mixed, glutaraldehyde is added to make the mass concentration of glutaraldehyde 1%. After cross-linking, the solution is immersed in a deionized water solvent or an ethanol solvent to remove impurities to obtain a double-network bone repair solution; the water content before freeze-drying is controlled to 90%, and the double-network bone repair material is obtained by freeze-drying after perfusion molding.

[0137] The freeze-drying conditions in this example were -20°C for 48 h.

[0138] Comparative Example 2

[0139] The preparation was carried out according to the formula amount of Comparative Example 1, which is different from Example 5 in that step 1) includes: preparing hydroxyapatite into a suspension according to the formula amount, adding it to a type I collagen slurry with a concentration of 5 mg / mL, adjusting the pH value of the solution to between 8 and 11 using a sodium hydroxide solution with a hydroxide ion concentration of 0.5 to 5 mol / L, adding glutaraldehyde to a mass concentration of 1%, and obtaining a hydroxyapatite cross-linked collagen solution after cross-linking.

[0140] The hydroxyapatite cross-linked collagen solution is soaked in deionized water solvent to remove impurities, and the water content is controlled to be 84-94%, and then freeze-dried and crushed to obtain raw material A with a particle size of 0.2-2 mm.

[0141] Comparative Example 3

[0142] The difference from Example 5 is that only the mineralized collagen powder is prepared, and the obtained mineralized collagen powder is used as a bone repair material.

[0143] Comparative Example 4

[0144] The difference from Example 5 is that only type I collagen slurry with a concentration of 5 mg / mL is used as the bone repair material after freeze-drying.

[0145] The bone repair materials in Examples 5 to 10 and Comparative Examples 2 to 3 are poured and molded into granules after freeze drying, which is only for the purpose of facilitating subsequent observation and detection of the structural characteristics and performance of the bone repair materials, but not for limiting them. In specific applications, they can be poured into different shapes according to needs, and then freeze dried and molded.

[0146] Test: Determination of physical and chemical parameters

[0147] 1) Take the material sample of Example 5 and measure its infrared spectrum: Take the freeze-dried sample and measure the infrared spectrum according to GB / T6040-2002 "General Rules for Infrared Spectroscopic Analysis Methods". The specific results are as follows: Figure 2 shown.

[0148] Depend on Figure 2 It can be seen that there are stretching vibration peaks of O-PO at 571cm-1 and 603cm-1, which indicates that hydroxyapatite is successfully synthesized and complexed with collagen to form mineralized collagen.

[0149] 2) Take the material sample of Example 5 and test it according to the "0451 X-ray diffraction method" (Pharmacopoeia 2020 edition) and compare it with the diffraction peak 09-0432. The specific results are as follows Figure 3 shown.

[0150] Depend on Figure 3It can be seen that compared with the diffraction peak 09-0432, the XRD peak type of the sample is basically consistent, and the main peaks exist, which shows that the generated substance is indeed hydroxyapatite.

[0151] 3) Take the material samples prepared in Example 5, Comparative Examples 2 and 3, observe the samples under a scanning electron microscope, and compare the internal pore sizes of the samples. The specific results are as follows: Figure 4 As shown, a is Example 5, b is Comparative Example 2, c is Comparative Example 3, and d is Comparative Example 4.

[0152] Depend on Figure 4 It can be seen that, compared with Comparative Examples 2 and 4, a mineralized layer is formed on the surface of Example 5, indicating that hydroxyapatite is deposited on the surface of collagen; compared with Comparative Example 3, a dense and porous double network structure is formed on the surface of Example 5.

[0153] 4) Take the material samples prepared in Examples 5 to 10 and Comparative Examples 2 to 4, and measure the porosity according to the following steps:

[0154] Fill the pycnometer with anhydrous ethanol, weigh the total mass of the pycnometer and ethanol and record it as W1, and immerse the previously weighed freeze-dried sample in ethanol, carefully wipe off the overflowed ethanol, weigh the weight of the pycnometer at this time and record it as W2, let it stand for 40 minutes, take out the sample, weigh the pycnometer and the amount of remaining ethanol and record it as W3, porosity = (W2 W3) / (W2 W1)*100%. The specific results are shown in Table 1.

[0155] 5) Take the material samples prepared in Examples 5 to 10 and Comparative Examples 2 to 4, make the samples into cylindrical shapes with a diameter of 10 mm and a height of 20 mm, measure their compressive strength on a dynamometer, and calculate the compressive strength. The specific results are shown in Table 1.

[0156] Table 1 Porosity and strength of different samples

[0157]

[0158]

[0159] It can be seen that when alginate is used as an antibacterial material, the mechanical properties of compressive strength obtained are relatively small; the preferred proportion of quaternized chitosan is Example 6; compared with Example 1, the sample obtained in Comparative Example 2 has a higher porosity and a lower strength, and it can be seen that the cross-linking bonding force between hydroxyapatite and the collagen layer is weak; the sample of Comparative Example 3 obtained by pure bone repair material has a higher porosity, but a relatively poor compressive strength; the sample prepared in Comparative Example 4 without hydroxyapatite has a higher porosity and a lower compressive strength.

[0160] 6) External antibacterial properties

[0161] The material samples of Example 5, Example 8 and Comparative Examples 2 to 4 were selected to measure their antibacterial properties according to the following method.

[0162] The antibacterial performance of the antibacterial repair material against Staphylococcus aureus and Escherichia coli was analyzed by diffusion plate method. First, 100 μl of bacterial solution (108 CFU·mL 1 ) was added to 100μl of PBS solution as a blank sample. At the same time, the bacterial liquid was dropped on the surface of bone repair materials and antibacterial bone repair materials as a control group. After incubating the bacterial suspension of each group with the culture solution for 1 hour, it was washed with 900μl PBS and 100μl of the bacterial suspension was applied to the culture dish (culture dish). After 24 hours of bacterial culture, the number of bacterial CFU was counted on the agar plate. In addition, an inhibition zone experiment was performed to further evaluate the sustainability of the inhibition. 200μl of Staphylococcus aureus and Escherichia coli (10 6 CFUmL 1 ) was evenly spread on the LB agar plate, and then the bone repair material and the antibacterial bone repair material were placed on the agar plate respectively. After being placed in a bacterial incubator for 24 hours, the diameter of the inhibition zone was measured. The specific results are shown in Figure 5 As shown, I is Comparative Example 3, II is Example 5, and III is Example 8.

[0163] Depend on Figure 5 It can be seen that compared with the bone repair material of comparative example 3, the antibacterial bone repair material has a certain antibacterial effect on Staphylococcus aureus and Escherichia coli. Among them, when the antibacterial material is chitosan, the killing effect is as high as 99%.

[0164] 7) In vitro degradation test

[0165] The material samples of Examples 5 to 8 and Comparative Examples 2 to 4 and hydroxyapatite (Comparative Example 5) were subjected to in vitro degradation tests. The in vitro degradation test process was as follows: 240 mL of the prepared Sorensen buffer (pH = 7.4) was evenly loaded into 24 beakers, one bracket was placed in each container, and the beakers were placed in a carbon dioxide incubator at 37°C ± 1°C. The buffer was changed every 7 days to keep the pH constant. Three samples were taken at 1 week, 1 month, and 2 months for visual observation and mass detection to calculate the degradation rate (the excess buffer was discarded and dried to constant weight in an electric blast drying oven). The degradation rate data are shown in Table 2.

[0166] Table 2 Degradation rates of different materials at different times in vitro

[0167]

[0168] As shown in Table 2, Examples 5 to 8 and Comparative Examples 2 to 3 can all be degraded by percentage, and their degradation efficiency is better than that of Comparative Example 5, but the degradation speed of Comparative Example 2 and Comparative Example 4 is too fast, which is not conducive to the growth of bone cells. Comparative Example 3 has a moderate degradation rate, but its compressive strength and antibacterial properties are poor.

[0169] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A double network antibacterial bone repair material, characterized in that: Includes mineralized collagen and antimicrobial materials; The mineralized collagen includes a collagen layer and mineralized hydroxyapatite deposited on the collagen layer; The antibacterial material and the collagen layer are cross-linked with each other.

2. The double network antibacterial bone repair material according to claim 1, characterized in that: The mass ratio of hydroxyapatite to collagen is 5:5 to 7:3; Preferably, the mass ratio of the antibacterial material to the mineralized collagen is 1:9 to 9:1; Preferably, the antibacterial material is modified chitosan, sodium alginate, betaine or curcumin; Preferably, the modified chitosan comprises at least one of acylated chitosan, carboxylated chitosan, alkylated chitosan or quaternized chitosan; Preferably, the collagen is type I collagen.

3. The method for preparing the double network antibacterial bone repair material according to claim 1 or 2, characterized in that: The following steps are involved: A. Adding calcium source and phosphorus source according to the formula amount into the collagen slurry to obtain mineralized collagen; B. Add mineralized collagen according to the formula amount into the antibacterial material solution for cross-linking to obtain a double-network antibacterial bone repair material.

4. The preparation method according to claim 3, characterized in that: The concentration of collagen in the collagen slurry is 1 to 10 mg / mL; Preferably, the molecular weight of the collagen is 10 to 200 kDa, preferably 120 to 140 kDa; Preferably, the adding of the calcium source and the phosphorus source comprises adding the calcium source and the phosphorus source while stirring; Preferably, the calcium ion concentration in the calcium source is 0.1 to 1 mol / L, and the phosphate ion concentration in the phosphorus source is 0.1 to 1 mol / L; Preferably, the molar ratio of the added calcium ions to phosphate ions is 2 to 4:2, preferably 3:2; Preferably, the rate of adding the calcium source and the phosphorus source is 0.01 to 10 g / min; the stirring speed is 50 to 800 rpm / min; Preferably, the calcium source includes at least one of calcium chloride, calcium bicarbonate, calcium bisulfate, calcium nitrate, calcium chlorate, calcium hypochlorite, calcium perchlorate, calcium bisulfite, calcium iodide, calcium bromide or calcium permanganate; Preferably, the phosphorus source includes at least one of phosphoric acid, sodium dihydrogen phosphate, trisodium phosphate or sodium hydrogen phosphate; Preferably, the concentration of the antibacterial material in the antibacterial material solution is 0.5 to 5 mol / L; Preferably, the mineralization further comprises freeze drying to obtain powdered mineralized collagen; Preferably, the particle size of the powdered mineralized collagen is 0.2-2 mm.

5. The preparation method according to claim 3, characterized in that: The mineralization conditions also include adjusting the pH value to 8 to 12, preferably 11.3, with alkali solution; Preferably, the hydroxide ion concentration in the alkali solution is 0.5 to 5 mol / L; Preferably, the collagen is type I collagen; Preferably, the water content of the mineralized collagen is controlled to be 84-94% before freeze-drying.

6. The preparation method according to claim 3, characterized in that: The antibacterial material comprises at least one of acylated chitosan, carboxylated chitosan, alkylated chitosan or quaternized chitosan; Preferably, freeze-drying is further included after cross-linking.

7. The preparation method according to claim 3, characterized in that: The cross-linking includes physical cross-linking or chemical cross-linking; Preferably, the chemical cross-linking comprises adding 0.1% to 5% of a cross-linking agent, preferably 1%; Preferably, the cross-linking agent comprises glutaraldehyde, genipin, vanillin, tannic acid or sodium tripolyphosphate, preferably glutaraldehyde; Preferably, the physical crosslinking is temperature crosslinking; Preferably, the temperature crosslinking is a dehydrogenation heat treatment; Preferably, the water content of the double network bone repair material is controlled to be 75-95% before freeze drying.

8. The preparation method according to claim 3, characterized in that: After mineralization and cross-linking, the method further includes soaking in deionized water or ethanol to remove impurities.

9. Use of the double network antibacterial bone repair material according to claim 1 or 2 or the double network antibacterial bone repair material prepared by the preparation method according to any one of claims 3 to 8 in bone tissue regeneration or as or in the preparation of bone defect filling and repair materials.

10. The use according to claim 9, characterized in that: The bone defect is a non-structural bone defect.

Citation Information

Patent Citations

  • Hydroxyapatite / chitosan composite material and preparation method and application thereof

    CN110575821A

  • Novel collagen and bioactive ceramic composite bone grafting material and preparation method thereof

    CN114588313A